Research on the exportable supply of SMEs in the La Matanza district (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
La Matanza is one of the districts located in the province of Buenos Aires, it is defined as the largest district. It is an important industrial center in Argentina, with a varied economy that includes sectors such as metallurgy, automotive, chemical and food and beverages. Being the most populated in the province of Buenos Aires, it contributes significantly to the industrial GDP of the region. The party's exports are mainly directed to Brazil, China, Chile, Uruguay and Paraguay, destinations that make up more than 70% of total exports. We will analyse the composition of the party's exports, the performance and evolution of these, during the period from 2019 to the first seven months of 2023, seeking a complete and current orientation of the exportable offer and the positioning of the party at an international level. Emphasis will be placed on the main exported products, their main destinations, the progress of exports during the analyzed period, and the most influential industrial sectors. Finally, the locations with the highest export activity and the companies that have stopped exporting in 2022 will be examined. This report has been created from a database of 339 companies located in the Municipality of La Matanza, which will be presented in this work.
Keywords: SMEs; financing; foreign trade; export performance